Investigation of molecular mechanisms regulating palmitate-induced metabolic inflexibility in a cell-based skeletal muscle model: physiological and pharmacological interventions. - Chien, Hung-Che (2020)
Background Present evidence indicates that increased systemic circulating fatty acids following chronic high-fat dietary intake leads to skeletal muscle (SKM) metabolic inflexibility, and this is associated with an impairment of the mitochondrial pyruvate dehydrogenase complex (PDC) controlled carbohydrate (CHO) oxidation. However, the molecular mechanisms behind the reduction in the PDC controlled CHO oxidation during chronic high-fat dietary intake are poorly understood. Nevertheless, previously published evidence advocated that transcription factors such as PPARα, PPARδ, and FOXO1 might contribute to the PDK4 mediated PDC inhibition. This thesis aimed, therefore, (1) to elucidate molecular and metabolic evidence supporting this contention in a metabolic inflexible C2C12 SKM cell model, and (2) to determine whether activators of CHO oxidation, such as exercise (delivered as electrical pulse stimulation - EPS), dichloroacetate (DCA) or R-α-lipoic acid (RALA) could rescue CHO oxidation in the presence of palmitate by altering the same molecular and metabolic events identified at (1). Results In chapter 3, we established what concentration of palmitate could be tolerated by our in vitro SKM cell model (500 M) without jeopardising the viability of the muscle cells. It was found in our SKM cell-based model that palmitate supplementation replicated well-defined markers of in vivo impaired cellular CHO oxidation: i.e. decreased glucose uptake, lower acetylcarnitine accumulation, lower pyruvate mediated mitochondrial ATP production rate, increased media lactate concentration and decreased PDC activity. It was also found that palmitate significantly increased the gene and protein expression of PDK4, PPARα, PPARδ, and FOXO1. In chapter 4, it was found that the palmitate-induced reduction in PDC activity could be reversed in tandem with a reduction in the PDK4 protein expression by siRNA PPARδ and FOXO1 gene silencing. It appeared, however, that although PPARα gene silencing restored the palmitate-induced reduction in PDC activity, this occurred independently from any changes in the PDK4 protein expression. siRNA PPARα, PPARδ, and FOXO1 gene silencing rescued the palmitate-induced reduction in the cellular glucose uptake. In contrast, only PPARδ and FOXO1 gene silencing reversed the palmitate-induced changes in media lactate and acetylcarnitine concentrations. The latter findings, which are in line with the contention these transcription factors are directly targeting PDC, also provide further evidence that the effects of PPAR on PDC activity occur independently of the involvement of PDK4 protein. Additionally, siRNA silencing of PPARα and FOXO1 restored the palmitate-induced reductions in the mitochondrial maximal ATP production rates (MAPR). In contrast, PPARδ silencing did not, surprisingly, rescue the palmitate-induced decline in MAPR. It was also found that the siRNA PPARδ gene silencing decreased FOXO1 protein expression. In contrast, the siRNA gene silencing of FOXO1 did not change the PPARδ protein expression, which collectively suggests that FOXO1 may be a PPARδ downstream target, thereby modulating PDK4 protein expression. In chapter 5, it was shown that administration of RALA or DCA rescued the palmitate-induced inhibition of PDC activity and the increase in media lactate concentration. However, only RALA corrected the deleterious effects of palmitate on cell glucose uptake and MAPR. At the molecular level, DCA, but not RALA, reduced PDK4 protein expression in the presence of palmitate. We also found that DCA and RALA reversed the palmitate-induced upregulation of PPARα and PPARδ and total-FOXO1 protein expression. In chapter 6, it was demonstrated that the treatment of palmitate-supplemented cells with electrical pulse stimulation (EPS) rescued the palmitate-induced dysregulation of glucose uptake, PDC activity, and its flux, and MAPR. Furthermore, these events were accompanied by a restoration/lowering of the protein expression levels of PPARδ and its downstream target FOXO1, but not those of PPARα and the p-FOXO1/t-FOXO1 ratio normalised to that of nuclear to cytoplasmic ratio. These molecular findings indicate benefits of sustained muscle contraction in maintaining CHO flux in the presence of palmitate. Conclusions This thesis provides persuasive evidence that the mechanism by which palmitate downregulates the PDC-mediated reduction in CHO oxidation in muscle occurs according to the following series of events: